Analisis Pendapatan Usahatani Tomat Pada Bekas Lahan Tidur Di Desa Taraitak Satu Kecamatan Langowan Utara - Brayen E. Aruperes; Rine Kaunang; Eyverson Ruauw (Sam Ratulangi University, 2022)
This study aims to analyze the income of tomato farming on former unused land in Taraitak Satu Village, North Langowan District, Minahasa Regency. This research was carried out for 3 months, starting from March to May 2021. The data collected in this study were primary data and secondary data. Sampling was carried out using a simple random sampling method of 10 respondents. The results showed that the income from respondent farmers with an average land area of 0.13 ha was Rp. 37,857,500, while the average total cost was Rp. 13,590,685, so that the total average income of farmers was Rp. 23,221,815. Tomato farming on a former idle land in Taraitak Satu Village received a production price BEP of Rp 120,271 per cash, so the situation was not profit or loss. In fact, the price per cash reached Rp 175,000 per cash, meaning the selling price was above the break-even point and the BEP production volume was obtained. production of 78 cash then the situation is not profit or loss in fact the production reaches 113 cash, this means that production is at the break-even point of production.